Isolation and Characterisation of Human-Derived blaKPC-3-Producing Salmonella enterica Serovar Rissen in 2018 - Daniela Fortini; Aurora García-Fernández; Claudia Lucarelli; Anna Maria Dionisi; Sergio Arena; Slawomir Owczarek; Michele Equestre; Alessandra Carattoli; Federica Sacco; Stefano Rossi; Roberta Ortenzi; Sara Primavilla; et al. (MDPI AG, 2023)
In this study, we describe a Salmonella enterica serovar (S.) Rissen strain with a reduced susceptibility to meropenem, isolated from a urinary infection in an 89-year-old woman in 2018 during activity surveillance in Italy (Enter-Net Italia). The genomic characteristics, pathogenicity, and antimicrobial resistance mechanisms were investigated via a genomic approach. Antimicrobial susceptibility testing revealed a "susceptible, increased exposure" phenotype to meropenem in the S. Rissen strain (4_29_19). Whole-genome sequencing (WGS) was performed using both the NovaSeq 6000 S4 PE150 XP platform (Illumina, San Diego, CA, USA) and MinION (Oxford Nanopore). The S. Rissen 4_29_19 strain harboured two plasmids: a pKpQIL-like plasmid carrying the blaKPC-3 resistance gene in a Tn4401a transposon (pKPC_4_29_19), and a ColE-like plasmid (p4_4_29_19) without resistance genes, highly prevalent among Enterobacterales. Comparative analysis revealed that the pKPC_4_29_19 plasmid was highly related to the pKpQIL reference plasmid (GU595196), with 57% coverage and 99.96% identity, but lacking a region of about 30 kb, involving the FIIK2 replicon region and the entire transfer locus, causing the loss of its ability to conjugate. To our knowledge, this is the first time that a pKpQIL-like plasmid, carrying blaKPC-3, highly diffused in Klebsiella pneumoniae strains, has been identified in a Salmonella strain in our country. The acquisition of blaKPC genes by Salmonella spp. is extremely rare, and is reported only sporadically. In zoonotic bacteria isolated from humans, the presence of a carbapenem resistance gene carried by mobile genetic elements, usually described in healthcare-associated infection bacteria, represents an important concern for public health.